ทาสสตรีผิวดำในนวนิยายอเมริกัน - มนฤดี เย็นบุตร (จุฬาลงกรณ์มหาวิทยาลัย, 2005)
This thesis aimed to analyse two important issues: first, the unique form of novels written by black female writers and second, the prejudices of race, social class and gender encountered by black female slaves. This thesis was based on four novels: The Bondwoman’s N a rrative (1850) by Hannah Crafts, OurNig (1859) by Harriet E. Adams Wilson, Inciden ts in the Life of a Slave Girl (1861) by Harriet Jacobs and Beloved (1973) by Toni Morrison. The result of the study showed that the novels written by the above writers have their own style depending on the writers’ background. These novels can be divided into three categories: the novel written by former slaves, the novel created by the writer was an indentured servant, and the novel composed by the writer who did not have direct experience of slavery. The content of these novels reflects the destiny of black female slaves who suffered from the prejudices of race, social class and gender as well as the portrait of life of black female slaves after being liberated. This portrait reveals their happiness after liberation, their suffering from pain caused by the haunting experience of slavery and their determination to continue their lives despite the existing prejudices in the outside world.